Functional neuroanatomy of vocalization in patients with Parkinson's disease - Rektorová, Irena; Mikl, Michal; Barrett, J; Mareček, Radek; Rektor, Ivan; Paus, T (Journal of the neurological sciences, 2012)
UNLABELLED: In Parkinson's disease (PD) both speech production and self-monitoring of voiced speech are altered. METHODS: In our previous study we used functional magnetic resonance imaging (fMRI) to examine which brain areas are involved in overt reading in nine female PD patients (mean age 66.0 ± 11.6 years) compared with eight age-matched healthy female controls (mean age 62.2 years ± 12.3). Here we performed the post-hoc seed-based functional connectivity analysis of our data to assess the functional connectivity between the periaqueductal gray matter (PAG; i.e. the core subcortical structure involved in human vocalization) and other brain regions in the same groups of PD patients and controls. RESULTS: In PD patients as compared with controls we observed increased connectivity between PAG and basal ganglia, posterior superior temporal gyrus, supramarginal and fusiform gyri and inferior parietal lobule on the right side. In the PD group, the connectivity strength in the right putamen and the right sypramarginal gyrus was correlated with variability of pitch while the connectivity strength in the right posterior superior temporal gyrus and in the right inferior parietal lobule was correlated with speech loudness. CONCLUSION: We observed functional reorganization in PD patients as compared with controls in both the motor basal ganglia-thalamo-cortical circuitry and cortical areas known to be engaged in-auditory and somatosensory feedback control of voiced speech. These changes were hemisphere-specific and might either reflect effects of dopaminergic treatment or at least partially successful compensatory mechanisms involved in early-stage PD.
Keywords: mapování mozku; magnetická rezonanční tomografie; Nerve Net; Aged; Periaqueductal Gray; senioři; čtení; Verbal Behavior; substantia grisea centralis; Reading; Brain Mapping; lidé; ženské pohlaví; verbální chování; Humans; nervová síť; Magnetic Resonance Imaging; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged